Different Risks of Mortality and Longitudinal Transition Trajectories in New Potential Subtypes of the Preserved Ratio Impaired Spirometry: Evidence From the English Longitudinal Study of Aging - He, Di; Sun, Yilan; Gao, Musong; Wu, Qiong; Cheng, Zongxue; Li, Jun; Zhou, Yong; Ying, Kejing; Zhu, Yimin (Frontiers in Medicine, 2021)
Background: Preserved Ratio Impaired Spirometry (PRISm), characterized by the decreased forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) with a preserved FEV1/FVC ratio, is highly prevalent and heterogeneous. We aimed to identify the subtypes of PRISm and examine their differences in clinical characteristics, long-term mortality risks, and longitudinal transition trajectories. Methods: 6,616 eligible subjects were included from the English Longitudinal Study of Ageing. Two subtypes of the PRISm were identified as mild PRISm (either of FEV1 and FVC <80% predicted value, FEV1/FVC ≥0.7) and severe PRISm (both FEV1 and FVC <80% predicted values, FEV1/FVC ≥0.7). Normal spirometry was defined as both FEV1 and FVC ≥80% predicted values and FEV1/FVC ≥0.7. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated by the multiple Cox regression models. Longitudinal transition trajectories were described with repeated spirometry data. Results: At baseline, severe PRISm had increased respiratory symptoms, including higher percentages of phlegm, wheezing, dyspnea, chronic bronchitis and emphysema than mild PRISm. During average 7.7 years of follow-up, severe PRISm significantly increased the risks of all-cause mortality (HR=1.91, 95%CI=1.58-2.31), respiratory mortality (HR=6.02, 95%CI=2.83-12.84), and CVD mortality (HR=2.11, 95%CI=1.42-3.13) compared with the normal spirometry, but no significantly increased risks were found for mild PRISm. In the two longitudinal transitions, mild PRISm tended to transition towards normal spirometry (40.2% and 54.7%), but severe PRISm tended to maintain the status (42.4% and 30.4%) or transition towards GOLD2-4 (28.3% and 33.9%). Conclusion: Two subtypes of PRISm were identified. Severe PRISm had increased respiratory symptoms, higher mortality risks, and higher probability of progressing to GOLD2-4 than mild PRISm. These findings provide new evidence for the stratified management of PRISm.